Distributional Patterns of Benthic Macro-invertebrate Fauna in the Glacier Fed Rivers of Indian Himalaya - Mishra, Asheesh Shivam; Nautiyal, Prakash; Semwal, Vijay Prakash (Our Nature, 2013)
Large-scale distributional pattern for the benthic macro-invertebrate fauna was determined in the glacier fed Himalayan and Trans-Himalayan rivers and streams of India at the elevation range of 2000-3000 m asl. In Trans-Himalaya the family Heptageniidae (Ephemeroptera) alone (Chandra and Bhaga) or in combination with Chironomidae (Diptera) in similar proportions (Chenab) or Diptera alone (Miyar) dominated the assemblages. Its influence seems to extend to Rupin drainage in the Himalaya where Chironomidae alone dominated the assemblages. Except for this Himalayan river. Various families of Trichoptera attained highest abundance in other rivers of the Himalaya. Thus, Leptoceridae in combination with Limnephilidae (Alaknanada at Tapovan) and Heptageniidae and Baetidae (Alaknanada at Mana) is the only instance of similarity in abundant taxa by virtue of same river. The Mandakini was partially similar to Alaknanda by virtue of abundant Limnephilidae. The Bhagirathi was characterized by abundance of Philopotamidae. Thus, assemblages exhibit greater variability in the Himalayan rivers than Trans-Himalayan rivers and are hence entirely different, as also evident from the cluster analysis. This present hypothesis is not applicable to explain the macro-invertebrate assemblages in Himalayan and Trans-Himalayan region. DOI: http://dx.doi.org/10.3126/on.v11i1.8242 Our Nature Vol.11(1) 2013: 36-44